Trends and socioeconomic inequalities in self-rated health in Japan, 1986-2016 - Hirokazu Tanaka; Johan P. Mackenbach; Yasuki Kobayashi (BMC, 2021)
Abstract Introduction Despite having very high life expectancy, Japan has relatively poor self-rated health, compared to other high-income countries. We studied trends and socioeconomic inequalities in self-rated health in Japan using nationally representative data. Methods The Comprehensive Survey of Living Conditions was analyzed, every 3 years (n ≈ 0.6-0.8 million/year) from 1986 to 2016. Whereas previous studies dichotomized self-rated health as an outcome, we used four categories: very good, good, fair, and bad/very bad. Proportional odds ordinal logistic regression models are used, with ordinal scale self-rated health as an outcome, and age category, survey year and occupational class or educational level as independent variables. Results In 2016, the age-adjusted percentages for self-rated health categorized as very good, good, fair, and bad/very bad, were 24.0, 17.1, 48.7, and 10.2% among working-age men, and 21.6, 17.5, 49.4, and 11.5% among working-age women, respectively. With 1986 as the reference year, the odds ratios (ORs) of less good self-rated health were lowest in 1995 (0.69; 95% Confidence Interval [95% CI]: 0.66-0.71 of working-age men), and highest in 2010 (1.23 [95% CI: 1.19-1.27]). The ORs of male, lower non-manual workers (compared to upper non-manual) increased from 1.12 (95% CI: 1.07-1.17) in 2010 to 1.20 (95% CI: 1.15-1.26) in 2016. Between 2010 and 2016, the ORs of working-age men with middle and low levels of education (compared to a high level of education) increased from 1.22 (95% CI: 1.18-1.27) to 1.34 (95% CI: 1.29-1.38), and from 1.47 (95% CI: 1.39-1.56) to 1.75 (95% CI: 1.63-1.88), respectively. The ORs of working-age women with middle and low levels of education also increased from 1.22 (95% CI: 1.17-1.28) to 1.32 (95% CI: 1.26-1.37), and from 1.74 (95% CI: 1.61-1.88) to 2.03 (95% CI: 1.87-2.21) during the same period. Conclusion Japan has the unique feature that approximately 50% of the survey respondents rated their self-rated health as fair, but with important variations over time and between socioeconomic groups. In-depth studies of the role of socioeconomic conditions may shed light on the reasons for the high prevalence of poor self-rated health in Japan.